Serum responsive proteome reveals correlation between oxidative phosphorylation and morphogenesis in Candida albicans ATCC10231 - Ahmed, Radfan; Kodgire, Santosh; Santhakumari, B.; Patil, Rajendra; Kulkarni, Mahesh J.; Zore, Gajanan (Journal of Proteomics, 2018)
To understand the impact of fetal bovine serum (FBS) on metabolism and cellular architecture in addition to morphogenesis, we have identified FBS responsive proteome of Candida albicans. FBS induced 34% hyphae and 60% pseudohyphae in C. albicans at 30 C while 98% hyphae at 37 C. LC-MS/MS analysis revealed that 285 proteins modulated significantly in response to FBS at 30 degrees C and 37 degrees C. Out of which 152 were upregulated and 62 were downregulated at 30 degrees C while 18 were up and 53 were downregulated at 37 degrees C. Functional annotation suggests that FBS may inhibit glycolysis and fermentative pathway and enhance oxidative phosphorylation (OxPhos), TCA cycle, amino acid and fatty acid metabolism indicating a use of alternative energy source by C. albicans. OxPhos inhibition assay using sodium azide corroborated the correlation between inhibition of glycolysis and enhanced OxPhos with pseudohyphae formation. C. albicans induced hyphae in response to FBS irrespective of down regulation of Rasl,Asrl/Asr2, indicates the possible involvement of MAPK and cAMP-PKA independent pathway. The Cell wall of cells grown in presence of FBS at 30 degrees C was rich in mannan, Beta 1,3glucan and chitin while membranes were rich in ergosterol compared to those grown at 37 degrees C. Significance of the study: This is the first study suggesting a correlation between OxPhos and morphogenesis especially pseudohyphae formation in C. albicans. Our data also indicate that fetal bovine serum (FBS) induced morphogenesis is multifactorial and may involve MAPK and cAMP-PKA independent pathway. In addition to morphogenesis, our study provides an insight in to the modulation of metabolism and cellular architecture of C. albicans in response to FBS.
Keywords: analysis; Candida albicans; Fetal bovin serum; Liquid chromatography mass spectrometry; morphogenesis; Oxidative phosphorylation; pathogenicity